Réponses

  • Utilisateur Brainly
2014-05-22T13:36:01+02:00
A=x²-9+(x+3)²;
  = (x-3)(x+3)-(x+3)²
  = (x+3)(x-3-x-3)
  = (x-3)(-6)
  = -6(x-3)
B=(x-2)²-(x²-4);
  =(x-2)²-(x-2)(x+2)
  = (x-2)(x-2-x-2)
  = (x-2)(-4)
  = -4(x-2)

C=(2x+3)(x+1)+4x²-9;
  =
(2x+3)(x+1)+(2x-3)(2x+3)
  = (2x+3)(x+1-2x+3)
  = (2x+3)(-x+4)

D=(x+1)²-(x-?)²;
  = manque

E=(x+1)²-9;
  = (x-1-3)(x-1+3)
  = (x-4)(x+2)

F=16-(x-1)²;
  = (4-x+1)(4+x-1)
  = (-x+5)(x+3)

G=(2x-5)²-(2x+3)²

   =(2x-5-2x-3)(2x-5+2x+3)
  = -8(4x-2)
  = -16(2x-1)